THE IMPLEMENTATION OF FOREST AND LAND FIRE MANAGEMENT POLICY IN INDONESIA DURING THE COVID-19 PANDEMIC - Afni Zukifli; Fara Merian Sari; Prihati Prihati (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2022)
The coronavirus outbreak (COVID-19) has raised questions about changes in subsequent environmental effects, mainly forest and land fires. This paper evaluates the implementation of land and forest fire management policies in Indonesia during the COVID-19 pandemic, particularly in 2020. A qualitative approach was conducted in policy implementation analysis based on George Edward III's theory by looking at bureaucratic structure, resources, communication, and disposition factors. The research focused on the operational work of the Forest and Land Fire Brigade, known as Manggala Agni, in Indonesia. The results showed that the collaborative work of Manggala Agni and the other forest and land fire task forces successfully reduced the hotspots; hence there was a significant decrease in the burned area. It is also inseparable from climatic factors. During this period there was no haze disaster although the task of controlling forest and land fires still encountered several obstacles during the pandemic. This is because of training, technology transfer, budget support, and synergy between stakeholders and Manggala Agni’s team members, so a significant reduction in forest and land fires during 2020 can be achieved.